A tellurylsulfide bond-containing redox-responsive superparamagnetic nanogel with acid-responsiveness for efficient anticancer therapy. Issue 98 (23rd November 2017) - Xia, Xiaoyang; Xiang, Xia; Huang, Fenghong; Zhang, Zhen; Han, Ling
Abstract : The tellurylsulfide bond (Te–S) as a reduction-responsive linkage was first exploited and investigated to achieve GSH-responsive drug release. Abstract : A tellurylsulfide bond-containing biopolymer nanogel was first fabricated to achieve smart drug release. The reductive nanogel exhibited highly sensitive reduction-responsiveness, fast internalization, and efficient anticancer therapy. This approach displays a new potential of tellurylsulfide bond-containing nanocarriers for drug delivery.